2008
DOI: 10.1210/en.2007-1659
|View full text |Cite
|
Sign up to set email alerts
|

Role for Inhibitor of Differentiation/Deoxyribonucleic Acid-Binding (Id) Proteins in Granulosa Cell Differentiation

Abstract: Recent studies in the hen ovary have linked the initiation of granulosa cell differentiation at follicle selection to the alleviation of inhibitory MAPK signaling. The present studies assessed a role for individual inhibitor of differentiation (Id) protein isoforms as modulators of key transcriptional events occurring within granulosa cells at or immediately subsequent to differentiation. Findings from freshly collected granulosa cells collected at different stages of follicle development demonstrated a negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
3
24
1
Order By: Relevance
“…These effects on ID expression are completely blocked by treatment with the selective MAP kinase/ERK inhibitor, U0126. We have recently provided evidence that changes in ID protein expression can modulate FSHR mRNA expression in undifferentiated granulosa cells (Johnson et al 2008a, Johnson & Woods 2009. In the present studies, BMP2 treatment was found to increase ID1, ID3, and ID4 expression (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…These effects on ID expression are completely blocked by treatment with the selective MAP kinase/ERK inhibitor, U0126. We have recently provided evidence that changes in ID protein expression can modulate FSHR mRNA expression in undifferentiated granulosa cells (Johnson et al 2008a, Johnson & Woods 2009. In the present studies, BMP2 treatment was found to increase ID1, ID3, and ID4 expression (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…3). This is noteworthy because treatment with BTC or TGFA was reported to increase ID1, ID3, and ID4 expression (and decrease levels of ID2) in undifferentiated granulosa cells (Johnson et al 2008a). These effects on ID expression are completely blocked by treatment with the selective MAP kinase/ERK inhibitor, U0126.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations